Separating Attention Deficit Hyperactivity Disorder and Learning Disabilities in Girls: A Familial Risk Analysis - Doyle, Alysa E.; Faraone, Stephen V.; DuPre, Emily P.; Biederman, Joseph (The American journal of psychiatry, 2001)
OBJECTIVE: Familial risk analysis was used to clarify the relationship in girls between attention deficit hyperactivity disorder (ADHD) and learning disabilities in either mathematics or reading. METHOD: The authors assessed the presence of ADHD and learning disabilities in 679 first-degree relatives of three groups of index children: girls with ADHD and a comorbid learning disability, girls with ADHD but no learning disabilities, and a comparison group of girls without ADHD. RESULTS: The risk for ADHD was similarly higher in families of ADHD probands with and without learning disabilities; both groups had significantly higher rates of ADHD than did families of the comparison girls. In contrast, only among relatives of ADHD probands with a learning disability was there a higher risk for learning disabilities. A strong (although statistically nonsignificant) difference emerged that suggested at least some degree of cosegregation of ADHD and learning disabilities in family members. There was no evidence of nonrandom mating between spouses with ADHD and learning disabilities. CONCLUSIONS: These results extend previously reported findings regarding the relationship of ADHD and learning disabilities to female subjects and raise the possibility that, in girls, the relationship between ADHD and learning disabilities is due to shared familial risk factors.